2019
DOI: 10.1002/bio.3589
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive spectrofluorometric method for the determination of ascorbic acid in pharmaceutical nutritional supplements using acriflavine as a fluorescence reagent

Abstract: An easily performed, specific, sensitive, rapid, reliable and inexpensive procedure for the spectrofluorometric quantitation of ascorbic acid was proposed using acriflavine as a fluorescence quenching reagent. The procedure was based on the determined quenching effect of ascorbic acid on the natural fluorescence signal of acriflavine and the reaction between ascorbic acid and acriflavine in Britton-Robinson buffer solution (pH 6) to produce an ion-associated complex. The reduction in acriflavine fluorescence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The low values of LOD indicated high sensitivity. [ 17 ] Comparison of the proposed method with various previously reported methods demonstrated its superiority (Table S2).…”
Section: Resultsmentioning
confidence: 86%
“…The low values of LOD indicated high sensitivity. [ 17 ] Comparison of the proposed method with various previously reported methods demonstrated its superiority (Table S2).…”
Section: Resultsmentioning
confidence: 86%
“…Acridine dyes like acriflavine are highly fluorescent natural compounds that can be used as derivatizing agents [ 34 ]. Acriflavine was used for estimation of compounds having pharmaceutical interest such as ascorbic acid [ 35 ]. CFZ is non-fluorescent and has a free carboxylic group that ionizes (forming an anion) under alkaline conditions (pH 8).…”
Section: Resultsmentioning
confidence: 99%
“…Solution pH is considered a critical parameter of the medium and is required to permit protonation of acriflavine and the reaction to proceed [8,9]. BRB has been investigated over the pH range of 3-10, and it was found that the optimum pH was 7 for both OLS and SUL (figure 3a).…”
Section: Buffer Ph and Volumementioning
confidence: 99%
“…At the specified pH, the positively charged nitrogen atom in acriflavine reacts with the carboxylate anion of OLS or SUL. Hence, electrostatic forces contribute to ion-pair complex formation, as illustrated in scheme 1 [8,9].…”
Section: Determination Of Quenching Mechanism and Stoichiometry Of The Reactionmentioning
confidence: 99%
See 1 more Smart Citation